2021
DOI: 10.18632/aging.203125
|View full text |Cite
|
Sign up to set email alerts
|

Formulated Chinese medicine Shaoyao Gancao Tang reduces NLRP1 and NLRP3 in Alzheimer’s disease cell and mouse models for neuroprotection and cognitive improvement

Abstract: Amyloid β (Aβ) plays a major role in the neurodegeneration of Alzheimer's disease (AD). The accumulation of misfolded Aβ causes oxidative stress and inflammatory damage leading to apoptotic cell death. Traditional Chinese herbal medicine (CHM) has been widely used in treating neurodegenerative diseases by reducing oxidative stress and neuroinflammation. We examined the neuroprotective effect of formulated CHM Shaoyao Gancao Tang (SG-Tang, made of Paeonia lactiflora and Glycyrrhiza uralensis at 1:1 ratio) in AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…A study by Daniels et al (2016) demonstrated that Fenamate NSAIDs improved the microglia-mediated neuroinflammation and memory loss in 3×TgAD mice by indirectly inhibiting the activation of NLRP3 inflammasome. Then, Chiu et al (2021) found that SG-Tang could act as a neuroprotective agent against Aβ aggregation and neuroinflammation by regulating the NLRP1/NLRP3 pathway. Subsequently, Kuwar et al (2021) suggested that loaded Aβ can be reduced significantly, alleviate neuroinflammation, improve hippocampal neuronal activity, and relieve cognitive function in APP/PS1 mice via inhibiting NLRP3 inflammasome with JC124.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Daniels et al (2016) demonstrated that Fenamate NSAIDs improved the microglia-mediated neuroinflammation and memory loss in 3×TgAD mice by indirectly inhibiting the activation of NLRP3 inflammasome. Then, Chiu et al (2021) found that SG-Tang could act as a neuroprotective agent against Aβ aggregation and neuroinflammation by regulating the NLRP1/NLRP3 pathway. Subsequently, Kuwar et al (2021) suggested that loaded Aβ can be reduced significantly, alleviate neuroinflammation, improve hippocampal neuronal activity, and relieve cognitive function in APP/PS1 mice via inhibiting NLRP3 inflammasome with JC124.…”
Section: Introductionmentioning
confidence: 99%
“…These include membrane glycoprotein CD200, fractalkine ligand CX3CL1, as well as various neurotrophins and other molecules. The investigation of the NLRP1 inflammasome gains even more importance when knowing that NLRP1 gene variants are associated with AD [ 28 ], whereas its silencing improves cognitive abilities and has a protective effect on neurons in animal models of AD [ 30 , 39 , 40 , 41 , 42 ]. In this study, we focused on the NLRP1 inflammasome, which had not been thoroughly analyzed before in AD, and to further assess the possible role of the inflammasome in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of the NLRP1 increases upon the addition of Aβ in neuronal cell cultures and is increasingly expressed in several animal models of AD [ 30 ]. Likewise, silencing the NLRP1 gene improves cognitive abilities and has a protective effect on neurons in animal models of AD [ 30 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo , pre-administration of ABPPk inhibits the activation of microglia in the CA3 region of the hippocampus, promotes the polarization of the microglia M2 phenotype, and reduces the expression of NLRP3, cleaved caspase-1 and ASC in the brain, thereby significantly improving the cognitive impairment of mice ( Ge et al, 2021 ). In addition, there are other Chinese herbal medicines, including Dl-3-n-butylphthalide (Dl-NBP) ( Wang et al, 2019 ), Shaoyao Gancao Tang (SG-Tang) ( Chiu et al, 2021 ), and Liquiritigenin (LG) ( Du et al, 2021 ), which can play a neuroprotective role in AD by inhibiting the NLRP3 inflammasome pathway. Therefore, these Chinese herbal medicines and extracts that can inhibit the activation of NLRP3 may be a promising and safe treatment for AD.…”
Section: Nlrp3 Inflammasome Inhibitors As a Potential Target For The ...mentioning
confidence: 99%